Characterization of low-pressure MWPC from 1E3 to 1E5 Pa. (27th April 2021) - Wang, Y.; Sun, Z.; Wang, X.; Yi, H.; Jiang, W.; Fan, R.; Zhou, L.; He, Y.; Ning, C.; He, Y.; Zhao, Y.; Sun, K.; et al.
Abstract: The LPMWPC can be used as the Δ E detector for the low-energy charged particle detection. In order to increase the transmittance, the wires were adopted as the cathode. This work investigated the LPMWPC signal characteristics of this configuration and measured the gas gain with a mixture of 90%Ar and 10% CO2 from 1E3 to 1E5 Pa. From the test, the second pulse after the avalanche signal was observed, which proved to be caused by the ions' drifting near the cathode wire.